(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Ustymenko-Kosorich O. A Musical and Pedagogical profile S. Mokranyat’s in the context of music education Serbia. The article outlines the musical and pedagogical context creativity S. Mokranyat’s in the process of Serbian music education. Educational, conductor, composer activity S. Mokranyat’s had a significant influence on the development of the national Serbian music. These conceptual musical and pedagogical ideas figure defined path forward his own music school of Serbia. Considered musically Яeducational tendencies of the music-school teacher Serbia in a particular historical and cultural order.